Intraguild predation between 'Euseius stipulatus 'and the phytoseiid predators of 'Tetranychus urticae' in clementines, 'Neoseiulus californicus and 'Phytoseiulus persimilis - Abad-Moyano, Raquel; Urbaneja, Alberto; Schausberger, Peter (2017)
The current management of the two spotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae) in clementines is based primarily on applications of acaricides. In recent years, emphasis has been placed on implementing more environmentally safe measures to control T. urticae in Spain. To this end, inoculative releases of the predator phytoseiids Neoseiulus californicus (McGregor) and Phytoseiulus persimilis Athias-Henriot are currently being implemented. Indeed, phytoseiid releases have demonstrated to be successful in controlling T. urticae on clementine under laboratory and semi-field conditions. Both phytoseiids are naturally present in the citrus agro-ecosystem although at low levels. However, Euseius stipulatus Athias-Henriot is the most abundant phytoseiid in citrus and its conservation is a key component in the citrus IPM, due to its positive action on different pests. Therefore, before using N. californicus and P. persimilis to control T. urticae in inoculative releases in commercial orchards, we need to clarify the relationship between these phytoseiid species. With this aim, we conducted two experiments of intraguild predation between E. stipulatus and N. californicus, and between E. stipulatus and P. persimilis. First, we tested the aggressiveness (propensity of an individual to attack and kill another individual) of adult females on hetero-specific larvae. Second, we assessed survival and development of immature individuals in presence and absence of intraguild adult predators and alternative food.